A new species of Saxifraga in section Ciliatae subsection Gemmiparae (Saxifragaceae) from Sichuan province, China - Gao, Qingbo; Zhang, Zhuoxin; Chen, Shilong; Gornall, Richard J. (Phytotaxa, 2018)
Saxifraga viridipetala Z-X. Zhang & Gornall (Saxifragaceae) is described as a new species. Originating from south-western Sichuan province in China, morphological and molecular evidence (based on chloroplast trnL-F and nuclear ITS DNA sequences) indicate that S. viridipetala is closely related to S. gemmipara, in section Ciliatae. The new species can be diagnosed by its narrowly elliptic, pale green petals spotted purple in the proximal 4/5 part.